2002
DOI: 10.21273/horttech.12.4.682
|View full text |Cite
|
Sign up to set email alerts
|

Using the SPAD 502 Meter to Assess Chlorophyll and Nitrogen Content of Benjamin Fig and Cottonwood Leaves

Abstract: A Minolta SPAD-502 leaf chlorophyll meter was used for nondestructive data collection on the chlorophyll and nitrogen (N) status of benjamin fig (Ficus benjamina) and cottonwood (Populus deltoides) to quantitatively evaluate foliage quality. The goal was to provide a specific calibration for interpreting SPAD data within a media study for each species. Triplicate SPAD readings were collected from each of six leaves, sampled from forty plants per spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 21 publications
(23 reference statements)
1
57
1
3
Order By: Relevance
“…2b). These were lower than the coefficients of determination obtained by Loh et al (2002) for P. deltoides (r 2 = 0.96 using a quadratic regression model) who achieved SPAD readings at the upper level of chlorophyll content in the high 30s to mid 40s, with some values exceeding 50 when sampling single fully expanded leaves.…”
Section: Relationship Of Spad Values With Total Chlorophyllcontrasting
confidence: 61%
See 3 more Smart Citations
“…2b). These were lower than the coefficients of determination obtained by Loh et al (2002) for P. deltoides (r 2 = 0.96 using a quadratic regression model) who achieved SPAD readings at the upper level of chlorophyll content in the high 30s to mid 40s, with some values exceeding 50 when sampling single fully expanded leaves.…”
Section: Relationship Of Spad Values With Total Chlorophyllcontrasting
confidence: 61%
“…In P. deltoides, Loh et al (2002) found a high relationship between SPAD values and chlorophyll (sampled from the first fully expanded leaf; r 2 = 0.96) but lower relationships when SPAD values were linked to N measurements (composite of six leaves per plant; r 2 = 0.42 at 5 months and r 2 = 0.26 at 9 months). Recently, in trembling aspen (P. tremuloides, Michx), Bonneville and Fyles (2006) showed a similar relationship between SPAD values and N reported as a coefficient of correlation of r = 0.63 (r 2 = 0.40).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Nitrogen influences on SPAD values and growth, which have been seen in other Populus studies (Loh et al 2002), were thought to be minor because all plots were similar for soil NO 3 -N (experiment wide mean 7.6 mg kg -1 ) and foliar total N (experiment wide mean 3.0%) (Tables 3, 4). Likewise, no differences were found with regards to soil and foliar K, Zn, and Cu (Tables 3, 4) or foliar P (Table 4).…”
Section: Tree Growthmentioning
confidence: 52%